2016
DOI: 10.4103/0973-029x.190957
|View full text |Cite
|
Sign up to set email alerts
|

Central mucoepidermoid carcinoma radiographically mimicking an odontogenic tumor: A case report and literature review

Abstract: Central mucoepidermoid carcinoma (CMC) of the jaw bones is a rare malignant salivary gland tumor of unknown pathogenesis, comprising about 4% of all mucoepidermoid carcinomas (MECs). Most cases are histologically classified as a low-grade tumor and radiographically appear as a well-defined unilocular or multilocular radiolucent lesion. Block resection or wide local excisions are the treatment of choice and patients usually show a good overall prognosis although a long-term follow-up is necessary. This report d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
2
1
Order By: Relevance
“…Usually, it appears as a unilocular or multilocular radiolucent lesion with sclerotic and well-defined margins. Da Silva et al [6] reported mixed radiopaque-radiolucent lesion in mandible, Chundru et al [7], Kechagias et al [8], reported multilocular radiolucent lesion in maxilla and Nallamilli et al [9] reported unilocular radiolucent lesion in mandible; whereas our case present unilocular radiolucent lesion.…”
Section: Microscopic Confirmation Of the Diagnosiscontrasting
confidence: 42%
“…Usually, it appears as a unilocular or multilocular radiolucent lesion with sclerotic and well-defined margins. Da Silva et al [6] reported mixed radiopaque-radiolucent lesion in mandible, Chundru et al [7], Kechagias et al [8], reported multilocular radiolucent lesion in maxilla and Nallamilli et al [9] reported unilocular radiolucent lesion in mandible; whereas our case present unilocular radiolucent lesion.…”
Section: Microscopic Confirmation Of the Diagnosiscontrasting
confidence: 42%
“…The clinical features of our case showed that biopsy is essential for diagnosis, and clinical diagnosis may be misleading. Therefore, oral lesions may mimic each other and present very different clinical manifestations (12). In addition, just only examining radiologic images does not lead us to correct diagnosis, but it is essential for a total examination.…”
Section: Discussionmentioning
confidence: 99%
“…Low-grade central mucoepidermoid carcinoma is typically treated through block resection, hemi-mandibulectomy, or hemi-maxillectomy, with or without additional treatment such as neck dissection or radiotherapy [24].…”
Section: Implications For Treatment Decisionsmentioning
confidence: 99%